Isolation, Culture, and Functional Characterization of Human Embryonic Stem Cells: Current Trends and Challenges - Firdos Alam Khan; Dana Almohazey; Munthar Alomari; Sarah Ameen Almofty (Stem Cells International)
Human embryonic stem cells (hESCs) hold great potential for the treatment of various degenerative diseases. Pluripotent hESCs have a great ability to undergo unlimited self-renewal in culture and to differentiate into all cell types in the body. The journey of hESC research is not that smooth, as it has faced several challenges which are limited to not only tumor formation and immunorejection but also social, ethical, and political aspects. The isolation of hESCs from the human embryo is considered highly objectionable as it requires the destruction of the human embryo. The issue was debated and discussed in both public and government platforms, which led to banning of hESC research in many countries around the world. The banning has negatively affected the progress of hESC research as many federal governments around the world stopped research funding. Afterward, some countries lifted the ban and allowed the funding in hESC research, but the damage has already been done on the progress of research. Under these unfavorable conditions, still some progress was made to isolate, culture, and characterize hESCs using different strategies. In this review, we have summarized various strategies used to successfully isolate, culture, and characterize hESCs. Finally, hESCs hold a great promise for clinical applications with proper strategies to minimize the teratoma formation and immunorejection and better cell transplantation strategies.